2010
DOI: 10.1159/000276372
|View full text |Cite
|
Sign up to set email alerts
|

Harm Avoidance as a Mediator of Treatment Response to Antidepressant Treatment of Patients with Major Depression

Abstract: Background: The temperament harm avoidance (HA) has consistently demonstrated an association with major depressive disorder (MDD), serotonin functioning and reduction in depression symptoms in response to antidepressant medications targeting the serotonin system. In the current investigation, we examine HA as a potential mediator of treatment response to a serotonergic tricyclic antidepressant. Methods: Outpatients (n = 150) with MDD were randomized to receive clomipramine or a control treatment. Patients comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
2
22
0
1
Order By: Relevance
“…Current literature suggests that the NGF rs6330 polymorphism affects anxiety-related personality traits in healthy controls (Lang et al, 2008). HA has also been found to mediate the therapeutic response to antidepressant in MDD (Quilty et al, 2010). These studies supported our finding that NGF variants may determine antidepressant efficacy, and this effect is partially mediated by HA in patients with MDD.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Current literature suggests that the NGF rs6330 polymorphism affects anxiety-related personality traits in healthy controls (Lang et al, 2008). HA has also been found to mediate the therapeutic response to antidepressant in MDD (Quilty et al, 2010). These studies supported our finding that NGF variants may determine antidepressant efficacy, and this effect is partially mediated by HA in patients with MDD.…”
Section: Discussionsupporting
confidence: 88%
“…Fourth, we did not measure posttreatment HA scores, and could not examine the correlation between the change in HA scores and NGF variants. However, a previous study has found that change in HA scores may be positively correlated with change in HDRS scores (Quilty et al, 2010).…”
Section: Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…Third, this is one of the few studies that systematically examines the confounding and moderating effects of a wide range of sociodemographic and clinical patient characteristics on the relationship between therapeutic alliance and subsequent clinical improvement, contributing to our understanding of individualized treatments. Recently, Quilty et al [35] found that personality (e.g. harm avoidance) mediated treatment response to medication targeting serotonergic functioning, thereby suggesting that personality constructs should also be taken into account when designing individualized treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of the symptom profile of patients resistant to antidepressants has been very limited with standard methods [203]. …”
Section: Discussionmentioning
confidence: 99%